Case report on an enigma of caesarean section: ‘scar endometriosis’ - Singh, Anamika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Endometriosis is described as a disease in which functional endometrial glands and stroma that commonly lines the uterus grows outdoor the uterus. The resulting cystic or solid tumoral masses due to endometriosis are named as endometrioma. They’re normally seen within the ligaments of uterus, ovaries, pouch of Douglas and pelvic peritoneum however endometriosis has additionally been noted in nose, breast, lung, spleen, gastrointestinal tract, kidney, abdominal wall, however scar endometriomas are extremely uncommon and difficult to diagnose. This situation may be puzzled with different surgical conditions, however imaging strategies and FNAC can assist in diagnosing it better. Medical treatment is helpful in selected cases but wide excision is the treatment of choice.